HUBUNGAN PENDAMPINGAN SLPHT TERHADAP PERUBAHAN PERILAKU PETANI PADI SAWAH DI DESA GLONGGONG, KECAMATAN NOGOSARI KABUPATEN BOYOLALI - Andi Walela; SUTARNO SUTARNO; SUSWADI SUSWADI (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2011)
The study was conducted in November until December 2009 at the Village Glonggong, District Nogosari, Boyolali .. The aim of research to find out the relationship to changes in behavior SLPHT assistance of Paddy Farmers in Sub Nogosari Boyolali The basic method used is descriptive analysis and in its implementation with a survey method. Determining the location intentionally (purposive), making farmers in proportion to sample random sampling. Collection of data was conducted by interview to farmers by collecting the questionnaires. Methods of data analysis to determine whether there is mentoring relationship to changes in behavior SLPHT rice farmers using analysis of Rank Spearman Correlation. Results of analysis shows: There is a relationship of matter with the skills of farmers; rice yield change; group dynamics; participation in management of group activities; and government involvement in the Field School, There is a relationship between the facilitator with the skills of farmers; rice yield change; group dynamics; participation in the management of group activities; and government involvement in the Field School, There is a relationship between the training process with a skilled farmer field school; the change of rice yield; group dynamics; participation in the management of group activities; and government involvement in the Field School, There is a relationship between training time farmer field school with the skills, group dynamics; participation in the management of group activities; and government involvement in the Field School; except for changes in rice yield, There is a relationship between the organization of farmer field school with the skills; changes in rice yield; group dynamics; participation in the management of group activities; and government involvement in the Field School, The relationship between the usefulness of the Field School with the skills of farmers; rice yield change; group dynamics; and participation in the management of group activities; except for government involvement in the Field School.